2021
DOI: 10.1097/dss.0000000000002995
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Current Medical and Surgical Treatment Options for Microstomia in Patients With Scleroderma

Abstract: BACKGROUND Most patients with scleroderma suffer from microstomia, which can have debilitating consequences on their quality of life. Unfortunately, treatment options remain limited. No specific guidelines exist; hence, microstomia remains a challenge to treat in this patient population. OBJECTIVE This review aims to evaluate the different medical and surgical treatment modalities currently available for microstomia in patients with scleroderma and make… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…Other syndromes have been described with microstomia, such as Richieri-Costa-Pereira syndrome, 14 Freeman-Sheldon Syndrome 15 or Scleroderma. 16 Previous reports have shown patients with similar characteristics to the patient presented in this report, such as deep bite, skeletal class II 17 or difficulties for taking impressions due to microstomia. 8 In patients with EB, Shah et al 18 suggested a reduced maxillary size caused by malnutrition and scarring tissue, leading to severe crowding.…”
Section: Discussionsupporting
confidence: 67%
“…Other syndromes have been described with microstomia, such as Richieri-Costa-Pereira syndrome, 14 Freeman-Sheldon Syndrome 15 or Scleroderma. 16 Previous reports have shown patients with similar characteristics to the patient presented in this report, such as deep bite, skeletal class II 17 or difficulties for taking impressions due to microstomia. 8 In patients with EB, Shah et al 18 suggested a reduced maxillary size caused by malnutrition and scarring tissue, leading to severe crowding.…”
Section: Discussionsupporting
confidence: 67%
“…1 Although immunomodulatory therapies are helpful for addressing visceral complications of scleroderma, they have not been demonstrated to be particularly efficacious in addressing cutaneous manifestations. 2…”
Section: Discussionmentioning
confidence: 99%
“…Other approaches include use of pulsed carbon dioxide laser, intense pulsed light, or ultraviolet A1 phototherapy, although evidence thus far is limited. 2 Recently, onabotulinumtoxin type A has been shown to be beneficial, possibly through paralysis of the orbicularis oris, inhibitory effects on fibroblasts, and increased expression of matrix metalloproteinases. 3…”
Section: Discussionmentioning
confidence: 99%
“…Current therapies consist of immunomodulating therapies; however, these are primarily intended for treating visceral manifestations and have demonstrated negligible effect in treating cutaneous symptoms. 1 There have been only two previous reports of the use of hyaluronidase for scleroderma-related microstomia. Both reports demonstrated improvement of oral aperture after sustained treatment over multiple sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Scleroderma is a chronic autoimmune disorder of connective tissue characterized by excess extracellular matrix production such as glycosaminoglycans such as hyaluronic acid. 1 These changes in the facial skin can result in smooth, taut, mask-like facies that cause psychological distress and decrease self-image. Microstomia is defined as an abnormally reduced oral aperture with an interincisal distance (IID) of less than 50 mm that causes functional impairment.…”
mentioning
confidence: 99%